What’s Trust Got to do With it? Lessons From Cross-Sectoral Research on Natural Resource Management in Australia and the U.S. - Toman, Eric Lee; Curtis, Allan Lindsay; Shindler, Bruce (Frontiers in Communication, 2021)
Natural resource management (NRM) is conducted within a complex context. This is particularly true at the interface of public and private interests where policy and management actions are often closely scrutinized by stakeholders. In these settings, natural resource managers often seek to achieve multiple objectives including ecosystem restoration, biodiversity conservation, commodity production, and the provision of recreation opportunities. While some objectives may be complementary, in many cases they involve tradeoffs that are contested by stakeholders. Substantial prior work has identified concepts related to trust as critical to the success of natural resource management particularly in cases of high complexity and uncertainty with high stakes for those involved. However, although regularly identified as a central variable of influence, trust appears to be conceptualized differently or entangled with related constructs across this prior research. Moreover, much of the research in NRM considers trust as an independent variable and considers the influence of trust on other variables of interest (e.g., acceptance of a particular management practices, willingness to adopt a best management practice). In this paper, we develop a conceptualization of trust drawing on different literature areas and consider how trust is related to constructs such as trustworthiness and confidence. We then consider trust in the context of natural resource management drawing on examples from the U.S. and Australia. We then consider implications of these findings for building trust in natural resource management.